And I darken - White, Kiersten (White, Kiersten. And I darken series, 2016)
In this first book in a trilogy a girl child is born to Vlad Dracula, in Transylvania, in 1435--at first rejected by her father and always ignored by her mother, she will grow up to be Lada Dragwlya, a vicious and brutal princess, destined to rule and destroy her enemies.